2005
DOI: 10.1063/1.2136150
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism in the angle-resolved C 1s photoemission spectra of gas-phase carvone enantiomers

Abstract: The inner-shell C 1s photoionization of randomly oriented molecules of the chiral compound carvone has been investigated using circularly polarized synchrotron radiation up to 30 eV above threshold. Binding energies of the C=O and CH2= carbon 1s orbitals were determined to be 292.8+/-0.2 and 289.8+/-0.2 eV, respectively. The remaining C-H C 1s levels substantially overlap under an intense central peak centered at 290.5+/-0.2 eV. The angle-resolved photoemission from the carbonyl carbon C=O core orbital in pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…The commonly used SFA fails in describing this effect, which leads to the conclusion that not only the orbital from which ionization takes place is important, but also the final scattering state of the emitted electron. This is in accordance with findings in the single-photon PECD, where an asymmetry occurs even with an achiral initial orbital, indicating that the scattering state plays a vital role in the process [39,40]. We have demonstrated that a rather simple approximation for the scattering state is sufficient to yield a nonzero PECD effect and thus to overcome a fundamental limitation of the plain SFA.…”
Section: Discussionsupporting
confidence: 76%
“…The commonly used SFA fails in describing this effect, which leads to the conclusion that not only the orbital from which ionization takes place is important, but also the final scattering state of the emitted electron. This is in accordance with findings in the single-photon PECD, where an asymmetry occurs even with an achiral initial orbital, indicating that the scattering state plays a vital role in the process [39,40]. We have demonstrated that a rather simple approximation for the scattering state is sufficient to yield a nonzero PECD effect and thus to overcome a fundamental limitation of the plain SFA.…”
Section: Discussionsupporting
confidence: 76%
“…As such it must be very largely uninfluenced by the handedness of the molecular framework within which it is located, especially so when, as in carvone, it is localized at some distance from the asymmetric carbon centre. Nevertheless, core level PECD 4,7 has been found to be at least comparable in magnitude to typical valence shell results. 8,9,11 …”
Section: Introductionmentioning
confidence: 58%
“…7,[11][12][13] At the same time the successful application of theoretical models to treat the experimental data provides clear evidence that not just molecular conformation, but also absolute configuration could be assigned with such experimental data.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a sudden approximation for the ionization the emitted HOMO and SHOMO electrons (single photon case) and the Rydberg electrons (multiphoton case) will scatter off the same two ion core potentials. The importance of such final state scattering in PECD is well established, 6,37 it is after all how the photoelectron from a strongly localised, essentially achiral initial orbital senses the chirality of the molecule as it departs. On the other hand, the initial orbital enters into the dipole matrix elements and is not without influence.…”
Section: Photoelectron Circular Dichroismmentioning
confidence: 99%